Pee wees : confessions of a hockey parent - Cohen, Rich (New York : Farrar, Straus and Giroux, 2021)
"An exploration of parenting, sports, and the suburbs, all through the sport of children's ice hockey"--
Keywords: Cohen, Rich; Cohen, Rich; Hockey for children -- Connecticut; Hockey -- Social aspects -- Connecticut; Competition (Psychology) -- Social aspects; Parent and child; SPORTS & RECREATION / General; Competition (Psychology) -- Social aspects; Hockey for children; Hockey -- Social aspects; Parent and child; Connecticut; Personal narratives